Model-Model Pengembangan Kurikulum: Tinjauan Konseptual (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Curriculum development is a strategic process involving various factors, ranging from value systems and student needs to educational policy orientations. This article discusses three curriculum development models: the Administrative model, the Grass Roots model, and the Interpersonal Relation model proposed by Carl Rogers. These models are analyzed based on their orientation, strengths, and limitations. The findings indicate that no model is universally applicable; rather, the choice of model should be tailored to the context and needs of each educational institution.